It's hard to play ball: A qualitative study of knowledge exchange and silo effects in public health - Rebecca Johnson; Amy Grove; Aileen Clarke (BMC, 2018)
Abstract Background Partnerships in public health form an important component of commissioning and implementing services, in England and internationally. In this research, we examine the views of staff involved in a City-wide health improvement programme which ran from 2009 to 2013 in England. We examine the practicalities of partnership work in community settings, and we describe some of barriers faced when implementing a large, multi-organisation health improvement programme. Methods Qualitative, semi-structured interviews were performed. Purposive sampling was used to identify potential participants in the programme: programme board of directors, programme and project managers and intervention managers. Interviews were conducted one-to-one. We conducted a thematic analysis using the 'one sheet of paper' technique. This involved analysing data deductively, moving from initial to axial coding, developing categories and then identifying emerging themes. Results Fifteen interviews were completed. Three themes were identified. The first theme reflects how poor communication approaches hindered the ability of partnerships to deliver their aims and objectives in a range of ways and for a range of reasons. Our second theme reflects how a lack of appropriate knowledge exchange hindered decision-making, affected trust and contributed to protectionist approaches to working. This lack of shared, and communicated, understanding of what type of knowledge is most appropriate and in which circumstance made meaningful knowledge exchange challenging for decision-making and partnership-working in the City-wide health improvement programme. Theme three demonstrates how perceptions about silos in partnership-working could be problematic, but silos themselves were at times beneficial to partnerships. This revealed a mismatch between rhetoric and a realistic understanding of what components of the programme were functional and which were more hindrance than help. Discussion There were high expectations placed on the concept of what partnership work was, or how it should be done. We found our themes to be interdependent, and reflective of the 'dynamic fluid process' discussed within the knowledge mobilisation literature. We contend that reframing normal and embedded processes of silos and silo-working already in use might ease resistance to some knowledge exchange processes and contribute to better long-term functioning of public health partnerships.